Women's entrepreneurship in the global south: Empowering and emancipating? - Funmi (Olufunmilola) Ojediran; Alistair Anderson (Administrative Sciences, 2020)
This paper addresses the following questions: Are women entrepreneurs empowered by entrepreneurship, and critically, does entrepreneurship offer emancipation? Our theoretical position is that entrepreneurship is socially embedded and must be recognized as a social process with economic outcomes. Accordingly, questions of empowerment must take full account of the context in which entrepreneurship takes place. We argue that institutions-formal and informal, cultural, social, and political-create gendered contexts in the Global South, where women's entrepreneurship is subjugated and treated as inferior and second class. Our thematic review of a broad scope of the literature demonstrates that in different regions of the Global South, women entrepreneurs confront many impediments and that this shapes their practices. We show how the interplay of tradition, culture, and patriarchy seem to conspire to subordinate their efforts. Yet, we also recognize how entrepreneurial agency chips away and is beginning to erode these bastions, in particular, how role models establish examples that undermine patriarchy. We conclude that entrepreneurship can empower but modestly and slowly. Some independence is achieved, but emancipation is a long, slow game.
Keywords: 350; women’ s entrepreneurship; institutions; freedom; independence; power